Can education compensate for low ability? Evidence from British data - Kevin Denny; Vincent O'Sullivan (University College Dublin, Department of Economics, 2004)
This paper uses cross section data to investigate whether education and ability are substitutes or complements in the determination of earnings. Using a measure of cognitive ability based on tests taken at ages 7 and 11 we find, unlike most of the existing literature, clear evidence that the return to schooling is lower for those with higher ability indicating that education can act as a substitute for observed ability. We also estimate quantile regression functions to examine how the return to schooling varies across the conditional distribution of earnings. The results show that the return is lower for higher quantiles, suggesting that education is also a substitute for unobserved ability.
hdl:10197/942
Keywords: J31; 330; earnings; education; ability; Bildungsniveau; Qualifikation; Bildungsertrag; Lohnniveau; Großbritannien